Antenatal care attendance and risk of low birthweight in Burkina Faso: a cross-sectional study - Mamadou Bountogo; Ali Sié; Alphonse Zakané; Guillaume Compaoré; Thierry Ouédraogo; Elodie Lebas; Jessica Brogdon; Fanice Nyatigo; Benjamin F. Arnold; Thomas M. Lietman; Catherine E. Oldenburg (BMC, 2021)
Abstract Background Low birthweight is a major contributor to infant mortality. We evaluated the association between antenatal care (ANC) attendance and low birthweight among newborns in 5 regions of Burkina Faso. Methods We utilized data from the baseline assessment of a randomized controlled trial evaluating azithromycin distribution during the neonatal period for prevention of infant mortality. Neonates were eligible for the trial if the weighed at least 2500 g at enrollment and were 8-27 days of age. Data on ANC attendance and birthweight was extracted from each child's carnet de santé, a government-issued health card on which pregnancy and birth-related data are recorded. We used linear and logistic regression models adjusting for potentially confounding variables to evaluate the relationship between ANC attendance (as total number of visits and ≥ 4 antenatal care visits) and birthweight (continuously and categorized into < 2500 g versus ≥2500 g). Results Data from 21,223 births were included in the analysis. The median number of ANC visits was 4 (interquartile range 3 to 5) and 69% of mothers attended at least 4 visits. Mean birthweight was 2998 g (standard deviation 423) and 8.1% of infants were low birthweight (< 2500 g). Birthweight was 63 g (95% CI 46 to 81 g, P < 0.001) higher in newborns born to mothers who had attended ≥4 ANC visits versus < 4 visits. The odds of low birthweight among infants born to mothers with ≥4 ANC visits was 0.71 (95% CI 0.63 to 0.79, P < 0.001) times the odds of low birthweight among infants born to mothers who attended < 4 ANC visits. Conclusions We observed a statistically significant association between ANC attendance and birthweight, although absolute differences were small. Improving access to ANC for all women may help improve birth outcomes. Trial registration The parent trial is registered at clinicaltrials.gov: NCT03682653 ; first registered 24 September 2018.